DINAMIKA POLITIK DI BALIK KEBIJAKAN UKT DI PRODI MPI UIN RADEN FATAH PALEMBANG DALAM MENIMBANG ULANG KEADILAN AKSES PENDIDIKAN TINGGI BAGI MAHASISWA - Fahmi; Muhammad Reyvalza Bayhaqi; Maida Rahma Wati; Alda Olyvia; Anna Mafiroh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The Single Tuition Fee (UKT) policy is a key instrument in higher education funding, aimed at creating a payment system that is fair, proportionate and commensurate with students’ financial means. However, in its implementation within the Islamic Education Management (MPI) programme at UIN Raden Fatah Palembang, this policy continues to raise various issues, particularly regarding perceptions of fairness, the transparency of UKT category determination, and an appeals mechanism that is considered suboptimal. This study aims to analyse the political dynamics in the implementation of the UKT policy and its impact on equitable access to higher education. The research method employed is a qualitative approach using data collection techniques such as observation, interviews, and documentation. The findings reveal a disparity in perceptions between the university administration and students regarding the UKT classification process, transparency of information, and the institution’s response to student appeals. Furthermore, campus political dynamics reveal power relations and a tug-of-war between institutional management efficiency and the principle of social justice in higher education. The study’s conclusion emphasises that the UKT policy requires a more participatory, transparent, and responsive evaluation to effectively support equitable access to higher education. It is hoped that the implications of this research will serve as a basis for consideration by higher education institutions in formulating